Students' Voices on E-Portfolio-Based English Listening Assessment Using Google Sites - Hanifa, Eisha Sabila Dieni; Yusuf, Fazri Nur; Gunawan, Muhammad Handi (JALL (Journal of Applied Linguistics and Literacy), 2024)
As assessment becomes more important in education, teachers must be advanced in both assessment and teaching course materials. The most recent way of assessing the performance of students in listening classrooms is value-added assessment using Google Sites as e-portfolios, one of among the strongest instruments used to assess the efficacy of teachers as well as recognise growth in students. Nonetheless, the use of e-portfolios in EFL students' listening classrooms and how it influences their learning enjoyment remains undetermined due to neither researchers nor students have addressed these issues in depth, and studies on using Google Sites as an e-portfolio-based assessment for teaching listening comprehensions have also been underutilised. Thus, this research aims to gain insight towards EFL students' views on using Google Sites as an e-portfolio-based value-added assessment tool in listening classrooms. It made use of a qualitative case study and included second-year university students. Students' course reflections and semi-structured interviews were both utilised to collect data, which was thereafter analysed qualitatively using coding and thematic analysis. The results of the study revealed that creating e-portfolios with Google Sites proves helpful in assessing students' learning achievement, tracking and measuring students' progress, and diagnosing deficiencies that need to be addressed. This study renders a recommendation for the use of other well-developed assessment tools in future studies.